Results-based financing: evidence from performance-based financing in the health sector - Amanda Melina Grittner (Deutsches Institut für Entwicklungspolitik (DIE), 2013)
Results-based approaches have been a focus of recent discussions in international development. This paper discusses if performance-based financing (PBF) can make foreign and domestic funding in the health sector more effective. It studies the experiences and data from PBF programmes in 13 developing countries in Africa, Asia and South America and evaluates their targeting mechanisms, incentive structure, effectiveness and efficiency. It finds that PBF may improve the effectiveness of healthcare supply and healthcare coverage, but that more monitoring and research are needed to evaluate its full potential. In the future research agenda, efforts should particularly focus on investigating the incentive structure of RBF more thoroughly – including non-monetary and perverse incentives –, on evaluating the effectiveness and efficiency of schemes more rigorously, and on studying the long-term effects of RBF.
Keywords: 330; Entwicklungsfinanzierung und öffentliche Finanzen; Öffentliche Finanzen; Wirksamkeit und Evaluierung